Authority of The Village Consultational Board in The Village Government System in Indonesia (State Administrative Law Review) - Miharja, Marjan; Irsan, Irsan; Suhariyanto, Didik; R. Pattipawae, Dezonda; Jazuli, H.E. Rakhmat (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Comprehensive regional autonomy implementation has far-reaching effects on all levels of administration, from the Regency to the City to the Village. As the Village Head, the Village Government is legally entitled to govern the Village. In order to better the lives of its citizens, the Village Head establishes policies and the Village Consultative Body implements them through the creation of Village Regulations. In order to better understand the Village Government System in Indonesia, this research will examine how the State Administrative Law evaluates the power of the Village Consultative Body. This study is normative in nature and takes a statutory approach to a literature-based research methodology. The findings confirmed that the Village Consultative Body was established to aid the Village administration in realizing the hopes and dreams of the local populace through the implementation of a more democratic form of administration. The creation of the Village Consultative Body has had a profound effect on the evolution of the idea of village government by delegating three areas of responsibility to it: the compilation and adoption of Village Regulations; the preparation of the Village Revenue and Expenditure Budget and financial management; and the selection of village apparatus. This is important since the concept of regional autonomy in Indonesia is grounded in theories of decentralization, authority, and monitoring.